The P-type ATPase inhibiting potential of polyoxotungstates. Issue 2 (9th January 2018) - Gumerova, Nadiia; Krivosudský, Lukáš; Fraqueza, Gil; Breibeck, Joscha; Al-Sayed, Emir; Tanuhadi, Elias; Bijelic, Aleksandar; Fuentes, Juan; Aureliano, Manuel; Rompel, Annette
Abstract : Polyoxometalates (POMs) are transition metal complexes that exhibit a broad diversity of structures and properties rendering them promising for biological purposes. Abstract : Polyoxometalates (POMs) are transition metal complexes that exhibit a broad diversity of structures and properties rendering them promising for biological purposes. POMs are able to inhibit a series of biologically important enzymes, including phosphatases, and thus are able to affect many biochemical processes. In the present study, we analyzed and compared the inhibitory effects of nine different polyoxotungstates (POTs) on two P-type ATPases, Ca 2+ -ATPase from skeletal muscle and Na + /K + -ATPase from basal membrane of skin epithelia. For Ca 2+ -ATPase inhibition, an in vitro study was performed and the strongest inhibitors were determined to be the large heteropolytungstate K9 (C2 H8 N)5 [H10 Se2 W29 O103 ] (Se2 W29 ) and the Dawson-type POT K6 [α-P2 W18 O62 ] (P2 W18 ) exhibiting IC50 values of 0.3 and 0.6 μM, respectively. Promising results were also shown for the Keggin-based POTs K6 H2 [CoW11 TiO40 ] (CoW11 Ti, IC50 = 4 μM) and Na10 [α-SiW9 O34 ] (SiW9, IC50 = 16 μM), K14 [As2 W19 O67 (H2 O)] (As2 W19, IC50 = 28 μM) and the lacunary Dawson K12 [α-H2 P2 W12 O48 ] (P2 W12, IC50 = 11 μM), whereas low inhibitory potencies were observed for the isopolytungstate Na12 [H4 W22 O74 ] (W22, IC50 = 68 μM) and the Anderson-type Na6 [TeW6 O24 ] (TeW6, IC50 = 200 μM). Regarding the inhibition of Na + /K + -ATPase activity, for the first time an ex vivo study was conducted using the opercular epithelium of killifish in order to investigate the effects of POTs on the epithelial chloride secretion. Interestingly, 1 μM of the most potent Ca 2+ -ATPase inhibitor, Se2 W29, showed only a minor inhibitory effect (14% inhibition) on Na + /K + -ATPase activity, whereas almost total inhibition (99% inhibition) was achieved using P2 W18 . The remaining POTs exhibited similar inhibition rates on both ATPases. These results reveal the high potential of some POTs to act as P-type ATPase inhibitors, with Se2 W29 showing high selectivity towards Ca 2+ -ATPase.